'I can do things that others can't': Civic policing as weaponized volunteering in eThekwini, South Africa. (March 2023) - Diphoorn, Tessa; Cooper-Knock, SJ
In this article, we analyse civic policing in post-apartheid South Africa as a form of 'weaponized volunteering'. We use 'weaponized volunteerism' as a conceptual lens to refer to practices that rest on the potentiality and/or willingness to use physical violence or to harness the physical violence of others under the guise of 'volunteer work'. By drawing from ethnographic fieldwork conducted by both authors in eThekwini, South Africa, we show that by framing civic policing as weaponized volunteerism, we are able to analyse the violence at the core of policing and underline the varied ways that violence work is harnessed and expanded through civic policing, in the interest of civic and state actors. This, in turn, allows us to explore the continuum between state and civic violence, which is often directed towards similar groups and individuals.